1996
DOI: 10.1007/bf00227174
|View full text |Cite
|
Sign up to set email alerts
|

Odor representation and discrimination in mitral/tufted cells of the rat olfactory bulb

Abstract: Extracellular single-unit responses to odorants with various properties were recorded from mitral/tufted cells over large areas of the olfactory bulb of anesthetized rats. Each cell was exposed to one stimulus set consisting of five different odorants each at five concentrations. The resulting concentration-response profiles were compared. All mitral/tufted cells examined responded to two or more odorants, and the largest proportion of the cells were sensitive to all five odorants. Cells unresponsive to all fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 58 publications
4
19
2
Order By: Relevance
“…In other studies, M/Ts responded to subsets of related compounds within a defined structural class, although selectivity across broader chemical categories was not addressed Mori et al, 1992;Katoh et al, 1993). Still other studies found relatively indiscriminate activation by various stimuli within small odorant panels (Motokizawa, 1996;Lehmkuhle et al, 2003Lehmkuhle et al, , 2006. Analogous neurons in the insect antennal lobe appear broadly tuned (Perez-Orive et al, 2002;Mazor and Laurent, 2005), although other insect findings support selectivity (Wang et al, 2003).…”
Section: Introductionmentioning
confidence: 89%
“…In other studies, M/Ts responded to subsets of related compounds within a defined structural class, although selectivity across broader chemical categories was not addressed Mori et al, 1992;Katoh et al, 1993). Still other studies found relatively indiscriminate activation by various stimuli within small odorant panels (Motokizawa, 1996;Lehmkuhle et al, 2003Lehmkuhle et al, , 2006. Analogous neurons in the insect antennal lobe appear broadly tuned (Perez-Orive et al, 2002;Mazor and Laurent, 2005), although other insect findings support selectivity (Wang et al, 2003).…”
Section: Introductionmentioning
confidence: 89%
“…However, this explanation appears unlikely, because reduction of NMDA transmission in urethane-anesthetized rats by various NMDA receptor antagonists does not lead to noticeable changes in the mitral cell spontaneous firing rate (Wilson et al, 1996). It is also true that anesthetics that have not been reported to block NMDA receptors, such as urethane, yield similar reductions in mitral cell spontaneous rate (Pager, 1983;Motokizawa, 1996;Kay and Laurent, 1999). We argue therefore that modulatory centrifugal inputs that are sensitive to the animal's state of vigilance, such as serotonin-containing fibers from the dorsal raphe nucleus and cholinergic fibers from the basal forebrain (Shipley and Ennis, 1996;Haberly, 2004), could modulate mitral cell spontaneous activity.…”
Section: Possible Neural Mechanismsmentioning
confidence: 99%
“…Therefore, the failure of these spatially (and temporally) unconstrained approaches to find evidence for tuning (c.f. : Motokizawa, 1996) cannot be taken as evidence that tuning of odorant responses does not occur.…”
Section: Possible Consequences Of Chemotopic Progressionsmentioning
confidence: 99%
“…It has been argued that this condition may have obscured a broader responsiveness of these cells than would have been detected if the animals were differently anesthetized (Motokizawa, 1996) or entirely awake (Bhalla and Bower, 1997;Kay and Laurent, 1999;Rinberg et al, 2006a). Awake animals, such as those we study using 2DG, show complex spontaneous mitral cell activity against which it appears to be easier to detect information about the animal's behavioral state (e.g., hunger, expectation of odor, alertness, or responses to any odor independent of its identity) than to detect information directly relevant to odor quality (Pager, 1974a,b;Bhalla and Bower, 1997;Kay and Laurent, 1999;Rinberg et al, 2006a), at least when the recordings are made in arbitrary locations in response to arbitrarily chosen odorants.…”
Section: Possible Consequences Of Chemotopic Progressionsmentioning
confidence: 99%